Genomic characterization of hypermucoviscous Carbapenem-resistant Klebsiella pneumoniae ST25 isolates from northwest Argentina - Dentice Maidana, Stefania (2022)
In recent years, an increase in the prevalence hypermucoviscous carbapenem-resistantKlebsiella pneumoniae with sequence type 25 (ST25) was detected in hospitals of Tucuman (Northwest Argentina). In this work, a comparative genomic analysis was performed with two K. pneumoniae ST25 strains (LABACER 01 and LABACER 27) to characterize the genes associated with virulence and host´s colonization. The complete genomes of K. pneumoniae LABACER 01 and LABACER 27 were sequenced with the Illumina MiSeq platform (Illumina Inc., San Diego, CA, USA) at INDEAR-BIOCERES (Rosario, Argentina), using a 2_150 bp read length sequencing protocol. Ribosomal Multilocus Sequence Typing (rMLST) was applied to the Klebsiella genomes and 32/51 genes encoding ribosomal protein subunits (rps) were recovered from the species K. pneumoniae and queried with the other Klebsiella genomes using the BLASTn algorithm. The sequences were concatenated with Mafft software and used for phylogenomic reconstruction with RAxML software. For the reconstruction of the phylogenetic tree, the GTR substitution model and 1000 bootstrap replications were used. Virulence factors associated with K. pneumoniae infections were retrieved from the NCBI database and compared across genomes using the BLASTp algorithm. Genomic analysis revealed that K. pneumoniae LABACER01 and LABACER27 possess virulence factors found in other strains that have been shown to be hypervirulent, including genes required for enterobactin (entABCDEF) and salmochelin (iroDE) biosynthesis. In both strains, the genes of toxin–antitoxin systems, as well as regulators of the expression of virulence factors and adhesion genes were also detected. Comparative genomics studies performed in this work also showed that the LABACER 01 and LABACER 27 strains possess unique virulence factors when compared to each other, the presence of tamA in the genome of LABACER 01 and not in LABACER 27 could be associated with the ability of the former to colonize the lungs and spread to the blood of infected mice more efficiently. On the other hand, K. pneumoniae LABACER 27 possesses the fimbriae genes yadV2, yadV3, and bfpA, associated with the ability of pathogenic E. coli strains to colonize abiotic surfaces, as well as to adhere to epithelial cells and even inhibit the phagocytic activity of macrophages. Our genomic study also detected the presence of the rfaH, copA, and aroE genes in the K. pneumoniae LABACER 27 genome, were rfaH and aroE are necessary to resist the microbicidal action of the complement system and copA to prevent the bactericidal effect of copper. Studies on the genetic potential of multiresistant K. pneumoniae strains as well as their cellular and molecular interactions with the host are of fundamental importance to assess the association of certain virulence factors with the intensity of the inflammatory response. In this sense, this work explored the virulence profile based on genomic and in vivo studies of hypermucoviscous carbapenem-resistant K. pneumoniae ST25 strains, expanding the knowledge of the biology of the emerging ST25 clone in Argentina.